Improving student resilience in the era new normal through group guidance using Cognitive Restructuring Techniques - Sri Hastuti; Firman Firman; Neviyarni Neviyarni; Rezki Hariko (Universitas Negeri Padang, 2022)
Today the world of education has changed from offline to online so that students cannot escape the crush that causes students to procrastinate a lot of assignments, be late in collecting assignments, cannot manage study time, do not dare to ask questions when they have difficulty understanding the subject matter, have difficulty understanding teacher instructions, students must provide quota packages, this causes students to like to complain, be confused, despair and give up easily, students are anxious, worried about missing lessons, and feel bored, this condition shows problems that come from resilience. Various crushes experienced by students in the new normal era have not been effective by being given group guidance to overcome it. Therefore, this study aims to (1) analyze differences in student resilience before being compared after taking group guidance using cognitive restructuring techniques, (2) analyzing differences before compared to after taking group guidance without special treatment, (3) analyzing differences in student resilience after attending group guidance using cognitive restructuring techniques compared to those following group guidance without special treatment.The research method used is quantitative research. This type of research is a Quasi Experiment Design with a pretest posttest control group design. The population in this study was 192 students, and 20 students were taken which were divided into 10 students for the experimental group and 10 students for the control group. Sampling used simple random sampling. The research instrument used was a Likert Scale model.The results showed that (1) there was a significant difference in student resilience before and after taking group guidance using cognitive restructuring techniques, (2) there was a significant difference in student resilience before and after taking group guidance without special treatment, (3) there was a significant difference resilience of students who follow group guidance using cognitive restructuring techniques and follow group guidance without special treatment. Therefore, group guidance on cognitive restructuring techniques is effective in increasing student resilience in the era new normal.